Estudio comparativo de los cambios dimensionales en la conservación de los patrones de núcleo en seco y húmedo elaborados en Pattern resin, Resin74 y Duralay. (2022)
The most important advances in the restoration of teeth, are related to the use of materials such as resins which should guarantee the durability and quality of the materials used in this activity. Objective: To evaluate the changes by means of the variables of conservation, time and processing material of the core patterns made of Pattern resin, Resin 74 and Duralay in wet and dry conditions. Materials and metho ds: Experimental, an in vitro study of core patterns of three brands most used in the clinical field at national level will be carried out and compared according to the variables of conservation, time and the material of manufacture, the sample is constitu ted by 18 samples of in vitro core pattern that will be elaborated on natural teeth (Premolars).Results: There are no statistically significant differences between the type of resin and the time, the type of conservation and the topography of the tooth. Co nclusions: dimensional changes do not occur in the operative process of the resins; they can occur in the origin laboratory.